Rethinking social theory / Roger Sibeon. - Sibeon, Roger, 1953- (Sage Publications, 2004)
[This book] provides a strong critique of the flaws in the field, developing a sustained argument for a revitalization of sociological theory as an academic discipline. The 1980s and 1990s witnessed the 'cultural turn' - a postmodern rejection of disciplinary knowledge in pursuit of the examination of culture - but here [the author] argues for a 'return' to a sociological theory and method that will facilitate worthwhile social knowledge. Comprehensive and ambitious, the book fuses theory and empirical matter, resulting in a compelling new contribution to the theoretical development of sociology and related disciplines. Drawing on the work of theorists such as Giddens, Mouzelis, Archer and Layder, and on a wide range of readings in contemporary social theory, [the author] explores unresolved controversies and ambiguities in today's sociological theorizing; critically examines four longstanding modes of social scientific thought - reductionism, essentialism, reification and functional teleology; develops a set of post-postmodern postulates and meta-concepts as resources for a multi-dimensional, multi-level (meta) theoretical and methodological framework. This book will interest academics and advanced students of sociology, social theory, social geography and political science.-Back cover.